Sources, Properties, and Pharmacological Effects of Quercetin - Ankit; Malviya, Rishabha; Sharma, Akanksha (Current Nutrition & Food Science, 2022)
The present review aims to describe an overview of quercetin with its various pharmacological effects. Quercetin is used as an antioxidant, anticancer, antibacterial and antimicrobial, anti-inflammatory, antidiabetic, antihypertensive, antifungal, anti-allergic, and antiproliferative agent, as described in the manuscript. It is mainly obtained from plant resources, which is also described in the manuscript. The manuscript also describes different studies related to quercetin, which shows various pharmacological activities. It is concluded from the study that quercetin has an efficacious effect on various diseases.
Keywords: antifungal agents